Radon Gas Adsorption Properties of Non-Cement Matrix Using Anthracite - Ung Lim, Hyun; Jeong Pyeon, Su; Soo Lee, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, research on minimizing the exposure of radon in human environment is under way due to the threat of exposure to radiation, which is a problem in the world.Methods/Statistical analysis: This study is about the production of Radon Radiation Absorbing Hardeners for radon - emitting materials in indoor environment of human body. The anthracite used as a conventional filter medium was used as a radon adsorbent and the characteristics of an adsorbed cured body for the replacement ratio of anthracite were analyzed.Findings: As a result of the analysis of the experimental results, the results of the measurement of the radon gas concentration are as follows. And the adsorption effect on the half - life period of 3.8 days of radon gas was investigated. The adsorption properties of radon gas showed similar tendency irrespective of the measurement period. The longer the period, the more the concentration of radon gas was constant.Improvements/Applications: As a result of this study, the concentration of radon gas tended to decrease as the anthracite replacement ratio increased, which was not related to the duration of the measurement period of 3 days and 7 days. It is considered that the average data analysis is needed through long-term measurement of radon gas, and additional experiments are required considering the space and spatial characteristics. In addition, performance evaluation of other adsorbents is also considered necessary.Â